Analysis of the Impact of Machinery and Equipment Assistance on the Income of Furniture and Handicraft SMEs in Palu City - Badria Badria; Andi Herman Jaya; Yunus Sading; Rita Yunus; Vera Sri Endah Cicilia (Transpublika Publisher, 2025)
Small and Medium Enterprises or commonly referred to as SME are production activities for goods used in daily human life. Production activities in this industry can serve as a means of employment absorption in a relatively short time and open job opportunities in a broader field. This study aims to determine the impact of machinery and equipment assistance on the income of SME Furniture and Crafts in Palu City. The research method used is quantitative research with a descriptive approach. The data collection method used is data obtained directly from respondents and data obtained from the Trade and Industry Office of Palu City. The analysis technique uses the Paired Sample t-Test. The results of this study show that the provision of machinery and equipment assistance from the government has a positive effect on the income of SME Furniture and Crafts.